Payment card rewards programs and consumer payment choice - Ching, Andrew T.; Hayashi, Fumiko (Journal of Banking & Finance, 2010)
By using a unique data set that contains detailed information about consumer payment choice and consumers’ attitudes toward each payment method, we estimate the effects of payment card rewards on consumer choice of payment methods. Our approach allows us to control for consumer heterogeneity. We find the effects of rewards to be statistically significant across five retail types. Our policy experiments suggest that for the sub-population who hold both credit and debit cards, removing rewards would increase their share of paper-based payment methods (i.e., cash and checks), measured in terms of in-store transactions, by no more than 4 percentage points.